Exosome–Liposome Hybrid Nanoparticles Deliver CRISPR/Cas9 System in MSCs. Issue 4 (30th January 2018) - Lin, Yao; Wu, Jiahua; Gu, Weihuai; Huang, Yulei; Tong, Zhongchun; Huang, Lijia; Tan, Jiali
Abstract: Targeted delivery of clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated protein 9 (Cas9) system to the receptor cells is essential for in vivo gene editing. Exosomes are intensively studied as a promising targeted drug delivery carrier recently, while limited by their low efficiency in encapsulating of large nucleic acids. Here, a kind of hybrid exosomes with liposomes is developed via simple incubation. Different from the original exosomes, the resultant hybrid nanoparticles efficiently encapsulate large plasmids, including the CRISPR–Cas9 expression vectors, similarly as the liposomes. Moreover, the resultant hybrid nanoparticles can be endocytosed by and express the encapsulated genes in the mesenchymal stem cells (MSCs), which cannot be transfected by the liposome alone. Taken together, the exosome–liposome hybrid nanoparticles can deliver CRISPR–Cas9 system in MSCs and thus be promising in in vivo gene manipulation. Abstract : Exosome is a promising drug delivery carrier limited by its low efficiency in encapsulating of large nucleic acids. Here, hybrid exosomes are produced through membrane fusion with liposomes and successfully deliver clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated protein 9 (Cas9) system in mesenchymal stem cells (MSCs), providing a new strategy for CRISPR/Cas9 system delivery and in vivo gene manipulation.